The value of ultrasonography in the diagnosis of early cirrhosis* - Galip ERSÖZ; Ulus Salih AKARCA; Funda YILMAZ; Ömer ÖZÜTEMİZ and Zeki KARASU and Tankut İLTER (Turkish Journal of Gastroenterology, 2019)
-